CHALLENGES AND OPPORTUNITIES OF POST-COVID HYBRID WORK MODEL - Vicente Cardoso, Gualdino Miguel de Jesus (Digital Repository of Theses - SSBM Geneva, 2023)
Covid 19 has changed the world in so many ways that most topics are still to be analysed. This research is based on a case study of an organization that recently adopted a hybrid working model once their workforce returned to this "new world". The objective was to identify what were the challenges managers were facing with this new work model and what they were doing to address these challenges. It adopted the case study as a research strategy and the method adopted is based on the scientific research process using a qualitative and quantitative methodology. Fifty-six managers answered fifteen questions survey. The data was then collated and analysed. Team cohesiveness, Cross-functional relationships, work monitoring, communication and motivation were identified as the top five challenges for managers that work under the adopted hybrid model. The research findings corroborate with other studies and authors. Although most of these studies were done for remote working, they still apply to the hybrid working model. Several versions of hybrid working are starting to be adopted by organisations, and many more will surface soon as companies adopt and adapt to their realities. The organisation used in the case study adopted the office-first hybrid model, and it was found that although the number of days away from the office was limited, Team cohesiveness and communication are still impacting the teams, and managers are mitigating these using several techniques. Nevertheless, 97% of the managers are of the view that the hybrid model of working is here to stay and will be widely adopted.